2002
DOI: 10.1038/nsb834
|View full text |Cite
|
Sign up to set email alerts
|

The 2.0 Å crystal structure of catalase-peroxidase from Haloarcula marismortui

Abstract: Catalase-peroxidase is a member of the class I peroxidase superfamily. The enzyme exhibits both catalase and peroxidase activities to remove the harmful peroxide molecule from the living cell. The 2.0 A crystal structure of the catalase-peroxidase from Haloarcula marismortui (HmCP) reveals that the enzyme is a dimer of two identical subunits. Each subunit is composed of two structurally homologous domains with a topology similar to that of class I peroxidase. The active site of HmCP is in the N-terminal domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
213
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(220 citation statements)
references
References 26 publications
5
213
2
Order By: Relevance
“…Indeed, it is clear that the catalatic function evolved as an adaptation of the peroxidatic function because the simple change of a tryptophan to a phenylalanine in the distal heme pocket reduces catalatic activity by 1000-fold (of Escherichia coli HPI) and increases peroxidatic activity by 3-fold (3)(4)(5). Furthermore, the core structures of both the N-and C-terminal domains of the catalase-peroxidases from Haloarcula marismortui and Burkholderia pseudomallei closely resemble the structure of plant peroxidases (6,7). Finally, the conversion of isoniazid into its active antitubercular form by KatG of Mycobacterium tuberculosis is clearly a result of the peroxidatic reaction using isonicotinic acid hydrazide (INH) 1 as a substrate that must mimic the actual in vivo substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is clear that the catalatic function evolved as an adaptation of the peroxidatic function because the simple change of a tryptophan to a phenylalanine in the distal heme pocket reduces catalatic activity by 1000-fold (of Escherichia coli HPI) and increases peroxidatic activity by 3-fold (3)(4)(5). Furthermore, the core structures of both the N-and C-terminal domains of the catalase-peroxidases from Haloarcula marismortui and Burkholderia pseudomallei closely resemble the structure of plant peroxidases (6,7). Finally, the conversion of isoniazid into its active antitubercular form by KatG of Mycobacterium tuberculosis is clearly a result of the peroxidatic reaction using isonicotinic acid hydrazide (INH) 1 as a substrate that must mimic the actual in vivo substrate.…”
mentioning
confidence: 99%
“…The structures of the catalase-peroxidases from H. marismortui and B. pseudomallei have been reported (6,7) and have revealed several features that are, so far, unique to this class of enzyme. Present in both structures is an unusual adduct or covalent linkage among the side chains of a tryptophan, a tyrosine, and a methionine (see Fig.…”
mentioning
confidence: 99%
“…There are three crystal structures of KatGs available, namely the Archaebacterium Haloarcula marismortui (5), Burkholderia pseudomallei (6), and Synechococcus PCC 7942 (PDB entry 1UB2), the latter being a cyanobacterial KatG with high homology to Synechocystis KatG. The structures show that the arrangement of the active site is similar to CcP and APX, containing the distal triad arginine, histidine, tryptophan, and the proximal triad aspartate, tryptophan, and histidine.…”
mentioning
confidence: 99%
“…An unprecedented covalent bond between the distal side tryptophan, tyrosine, and methionine residues (in Synechocystis numbering Trp 122 , Tyr 249 , and Met 275 ) was proposed to be present in the H. marismortui enzyme (5). A mass spectrometric analysis of the tryptic peptides from recombinant wild-type KatG and the tryptophan, tyrosine, and methionine variants of Synechocystis (7) and B. pseudomallei (8) confirmed that this novel covalent adduct really exists in solution and thus may be a common feature to all catalase-peroxidases.…”
mentioning
confidence: 99%
“…the superfamily of peroxidases from archaea, bacteria, fungi, and plants and the superfamily of animal peroxidases). Despite the availability of crystal structures (1)(2)(3)(4), no structural bases for the high catalase activity of KatGs has been assigned so far. Whether in KatGs compound I plays a similar role in the catalase cycle as in monofunctional catalases (EC 1.11.1.6; see (5) is not clear at the moment.…”
mentioning
confidence: 99%